Efficacy of aerobic granular sludge treatment of piggery wastewater under length regulation of truncated modified basalt fibers - Zhou, Yun; Soares, Ana; Wang, Xiaochun; Wu, Zhiren; Zhou, Xiangtong; Liu, Jianxun (Elsevier, 2025)
Aerobic granular sludge (AGS) technology offers several advantages over traditional activated sludge systems; however, its performance can be unstable when treating wastewater with high organic and ammonia loads. Truncated modified basalt fibers (TMBF) have been demonstrated to enhance the stability of AGS systems when treating piggery wastewater (PWW), but little is understood about their impact. In this study, the addition of TMBF with lengths ranging from 0.1 to 0.4 mm significantly accelerated sludge granulation, achieving complete granulation in 10 days compared to 17 days in the control reactor. The enhancement was attributed to increased secretion of β-polysaccharides, resulting in smaller cavities within the granules for the 0.1 mm TMBF. In contrast, 0.2 mm TMBF promoted the secretion of proteins, hindering substrate transfer and reducing ammonia oxidation efficiency. The addition of 0.1 mm TMBF resulted in chemical oxygen demand (COD) and ammonia removals of 90.7 % and 96.8 %, respectively. Furthermore, the addition of TMBF enriched the sludge with a substantial number of functional bacteria, Thauera and Chryseolinea, which were the most abundant genus, contributing to its stable pollutant removal efficiency. These findings provide key insights on potential strategies for optimizing AGS technology to treat industrial wastewater that has high ammonia and COD loads, not usually suited for intensified AGS systems.
Keywords: Aerobic granular sludge; Piggery wastewater; Truncated modified basalt Fiber; Stability; Granulation; 40 Engineering; 4004 Chemical engineering; 4005 Civil engineering; 4011 Environmental engineering